Purification and Evaluation of N-benzyl Cinnamamide from Red Seaweed Gracilaria fisheri as an Inhibitor of Vibrio harveyi AI-2 Quorum Sensing - Kulwadee Karnjana (Marine Drugs, 2020)
Previously, we reported that the ethanol extract from red seaweed Gracilaria fisheri effectively decreased biofilm formation of Vibrio harveyi. In this study, the anti-biofilm active compounds in the ethanol extract were isolated and their structures identified. The anti-biofilm fractionation assay for minimum inhibitory concentration (MIC) produced two fractions which possessed maximal inhibitory activities toward the biofilm formation of V. harveyi strains 1114 and BAA 1116. Following chromatographic separation of the bioactive fractions, two pure compounds were isolated, and their structures were elucidated using FTIR, NMR, and HR-TOF-MS. The compounds were N-benzyl cinnamamide and α-resorcylic acid. The in vitro activity assay demonstrated that both compounds inhibited the biofilm formation of V. harveyi and possessed the anti-quorum sensing activity by interfering with the bioluminescence of the bacteria. However, the N-benzyl cinnamamide was more potent than α-resorcylic acid with a 10-fold lesser MIC. The present study reveals the beneficial property of the N-benzyl cinnamamide from the ethanol extract as a lead anti-microbial drug against V. harveyi.